Strategies of retail business in response to the economic crisis : case study of the Central Group - Ornanong Chaicharoen; Buchel, Bettina; Tang, John C.S.; Becther, Clemens; Partial Scholarship (Bangkok : Asian Institute of Technology, 1998)
As a result of the bursting of the "economic bubble" in mid 1997, most businesses and the general population were confronted with decreasing liquidity. This had a significant impact on the Thai retailing industry. This research took Central Department Store (Central) as a case study to analyze and aimed to develop competitive strategies for it in the context of the change in its environment. It starts with an exhaustive review of literature and the framework of analyzing the industry and competitiveness. Subsequently, an external and internal analysis is carried out to identify the opportunities and threats, as well as the strengths and weaknesses of Central given the market situation in which it is operating. Based on the results of the analysis, a range of alternatives for competitive strategies are developed and recommended to the company.
A research report submitted in partial fulfillment for the degree of Master Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1998
Keywords: Retail trade; Financial crises